A Study of Working Capital Management in Tata Steel - Saxena, Yogesh Kumar (Journal of Commerce and Trade, 2017)
A business organization should determine the exact requirement of working capital and maintain the same evely through out the operating cycle. It is worth mentioning that a firm should have neither excess nor inadeuqate working capital as both the phenomena of over capitalization and under capitalization of working capital generate adverse effects on the profitability and liquidity of the concerned firm. Thus, some amount of cash is blocked in raw materials, WIP, finished goods, and sundry debtors and day to day cash requirements. However some part of current assets may be financed by the current liabilities also. Tata Steel Limited (formerly Tata Iron and Steel Company Limited (TISCO)) is an Indian multinational steel-making company headquartered in Mumbai and a subsidiary of the Tata Group. The study of working capital is based on tools like Trend Analysis, Ratio Analysis, Working Capital Leverage, Operating Cycle etc. Further the study is based on last three years’ Annual Reports of TATA STEEL Pvt. Ltd. The study has been conducted on working capital, ratio analysis, working capital leverage, working capital components which helped the company to manage its working capital efficiency and affectively.